MON-088 Impact of Vertebral Fracture on Auxological Profile and Insulin-Like Growth Factors of Children After Acute Lymphoblastic Leukemia Treatment - Ahn, Moon Bae (J Endocr Soc, 2020)
Purpose: To investigate the overall prevalence of vertebral fractures (VF) following childhood acute lymphoblastic leukemia (ALL) treatment and examine the association of VF with growth trajectory and insulin-like growth factors. Methods: Children (n=172; 59.3 % male) diagnosed with ALL at age between 2 and 18 years were assessed for VF by screening the lateral thoracolumbar spine radiographs (Genant’s semi-quantitative method) when treatment was completed (baseline). Anthropometric measurements between pre- to post-treatment period were obtained and the association of VF with insulin-like growth factor-1 (IGF-1) and insulin-like growth factor binding protein-3 (IGFBP-3) were examined. Results: Thirty-five children (20.3 %) had vertebral fractures at baseline. Among children with vertebral fractures, 97.1 % had either mild or moderate deformity, and the 5th lumbar vertebrae was the most frequently injured site (20.0 %). Median lumbar spine bone mineral density Z-score was -1.0 (IQR of -1.6 and -0.8) in children with VF. Baseline Z-scores for height and weight were lower in children with VF than without VF (-0.5±1.3 and 0.0±0.9, P=0.01; -0.2±1.6 and 0.3±1.1, P=0.04, respectively). Height Z-score in children with VF had greater height decline than without VF (0.5±0.6 and 0.2±0.8; P=0.02). Children with VF had lower IGF-1 and IGFBP-3 Z-score than without VF at baseline (-1.2±1.0 and 0.0±0.8, P<0.01; -2.3±1.1 and -1.3±1.0, P<0.01). Decrease in IGF-1 level was associated with the presence of VF (OR=0.3(95 % CI of 0.2-0.5), P<0.01). Conclusion: Substantial number of children encounter VF after ALL treatment is completed and the presence of VF might be associated with compromised auxological state, prominent height decline and IGF-1 deficiency.